Structure Based Antibody-Like Peptidomimetics - Mark I. Greene; Ramachandran Murali (MDPI AG, 2012)
Biologics such as monoclonal antibodies (mAb) and soluble receptors represent new classes of therapeutic agents for treatment of several diseases. High affinity and high specificity biologics can be utilized for variety of clinical purposes. Monoclonal antibodies have been used as diagnostic agents when coupled with radionuclide, immune modulatory agents or in the treatment of cancers. Among other limitations of using large molecules for therapy the actual cost of biologics has become an issue. There is an effort among chemists and biologists to reduce the size of biologics which includes monoclonal antibodies and receptors without a reduction of biological efficacy. Single chain antibody, camel antibodies, Fv fragments are examples of this type of deconstructive process. Small high-affinity peptides have been identified using phage screening. Our laboratory used a structure-based approach to develop small-size peptidomimetics from the three-dimensional structure of proteins with immunoglobulin folds as exemplified by CD4 and antibodies. Peptides derived either from the receptor or their cognate ligand mimics the functions of the parental macromolecule. These constrained peptides not only provide a platform for developing small molecule drugs, but also provide insight into the atomic features of protein-protein interactions. A general overview of the reduction of monoclonal antibodies to small exocyclic peptide and its prospects as a useful diagnostic and as a drug in the treatment of cancer are discussed.